Polytriphenylamine ketone compound, preparation method thereof and application of polytriphenylamine ketone compound in detection of drugs and explosives
The preparation of D-A polytrianiline ketone compound by one-step method is solved, and the problem of complex preparation of tripaniline fluorescent probes is achieved, and the high sensitivity detection of TNT in drugs and water is achieved, with good Anti-interference capability and low detection limit.
Patent Information
- Application Number
- CN202411379210.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2024-12-17
AI Technical Summary
The preparation steps of existing triphenylamine fluorescent probes are complex, have low quantum yields, insufficient sensitivity to budesonide suspension and TNT detection, high detection limits, and difficult to achieve large-scale production in water.
The D-A type polytrianiline compound was prepared by one-step C-N coupling reaction method, and the reaction of 4,4'-difluorobenzophenone and diarrhoimine compounds under a nitrogen atmosphere was prepared to produce high fluorescence responsiveness and A polymer with anti-interference ability, used for TNT detection in drugs and water bodies.
High sensitivity detection of TNT in drug budesonide suspension and water is achieved, with low detection limit and no influence from other nitro compounds and metal cations. The preparation method is simple and the yield is high.
Smart Images

Figure CN119143987A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of drug detection and water environment detection, and specifically relates to a DA type polytriphenylamine ketone compound and a preparation method thereof and application in drug detection and water environment explosive detection. Background Art
[0002] Drug quality control is the key to ensuring drug efficacy, so precise control of drug dosage and detection of impurity content in drugs have become a key process to ensure drug quality. For drugs such as budesonide suspension, the use of fluorescence detection methods is expected to control quality.
[0003] On the other hand, 2,4,6-trinitrotoluene (TNT) is a high explosive that is widely used. However, TNT is biologically toxic, difficult to degrade, and can cause irreversible destructive effects on the environment, so it is particularly important to monitor TNT in the environment.
[0004] In recent years, in the face of drug quality control and the detection challenges of nitroaromatic pollutants such as TNT in water, various instrument-based analytical techniques have developed rapidly, covering chromatography, mass spectrometry, gas chromatography-mass spectrometry, X-ray imaging, Raman spectroscopy, ion mobility spectrometry, electrochemical analysis and other methods. The emergence of these technologies has greatly promoted the progress of detection technology. However, these devices are often bulky and difficult to carry, making it difficult to meet the needs of real-time and on-site monitoring, especially in outdoor environmental monitoring situations where data needs to be obtained quickly. This limitation not only reduces the efficiency of on-site detection, but also increases the feedback time. In contrast, fluorescence-based detection methods have been used in portable detection equipment as early as the last century due to their simple operation, low cost, high sensitivity and excellent selectivity, and have therefore been widely used.
[0005] As a classic organic semiconductor material, triphenylamine shows great potential in the construction of fluorescent probes due to its unique electron-rich properties, geometric configuration and chemical stability. However, the current triphenylamine-based fluorescent probe materials face many challenges, such as complex synthesis, low yield and difficulty in large-scale production.
[0006] Typically, the synthesis of triphenylamine polymers requires the introduction of reactive functional groups in advance, followed by polymerization reactions. This method inevitably involves more synthesis steps and higher costs. In addition, unmodified triphenylamine polymers exhibit low quantum yields in aqueous media, and usually require modification with aggregation-induced emission (AIE) groups such as tetraphenylethylene to enhance the luminescence efficiency of the aggregated state. This limitation seriously affects the application of triphenylamine polymers as fluorescent probes for TNT in water.
[0007] Therefore, how to provide a preparation method for triphenylamine polymers with a simple preparation method, high yield, good responsiveness to drugs such as budesonide suspension, low detection limit for TNT in water, good anti-interference ability, and almost no influence by other nitro compounds and metal cation potential factors has become a technical problem to be solved urgently. Summary of the invention
[0008] The present invention aims to solve the above technical problems, thereby providing a DA type polytriphenylamine ketone compound and its application in drug detection and detection of explosive TNT content in water bodies, so as to solve the problems of the existing triphenylamine polymers, such as complicated preparation steps, low quantum yield, insufficient detection sensitivity for budesonide suspension and TNT, and high detection limit.
[0009] In order to achieve the above technical objectives, the technical solution adopted by the present invention is as follows:
[0010] The present invention first provides a DA-type polytriphenylamine compound, the structural formula of the DA-type polytriphenylamine compound is shown in the following formula <Ⅰ>:
[0011]
[0012] Wherein, Ar1 is Ar2 is X is n is a repeating unit.
[0013] Furthermore, the average lifetime <τ>avg of the DA-type polytriphenylamine compound is 1.29 to 1.67, and the fluorescence quantum yield in water is It is 0.01~0.06.
[0014] Furthermore, the thermal decomposition temperature of the DA type polytriphenylamine compound is 339-536°C, and the glass transition temperature is 160-193°C.
[0015] Furthermore, the DA-type polytriphenylamine ketone compound has a fluorescence quenching response to the drug budesonide suspension, and the detection limit of the DA-type polytriphenylamine ketone compound (PTPAK-2) for TNT is 0.25 μmol / L, and is almost not affected by other nitro compounds and metal cation potential factors.
[0016] The second object of the present invention is to provide a method for preparing the DA type polytriphenylamine ketone compound as described above, which is prepared in a one-step manner by CN coupling reaction with 4,4'-difluorobenzophenone, diaromatic imine compounds and potassium carbonate under a nitrogen atmosphere.
[0017] Furthermore, the diaromatic imine compound includes N,N'-diphenylbenzidine, N,N'-diphenyl-p-phenylenediamine or N,N'-di(2-naphthyl)-p-phenylenediamine.
[0018] Furthermore, the molar ratio of the 4,4'-difluorobenzophenone to the diaromatic imine compound is 1:1.
[0019] Furthermore, the molar ratio of the 4,4'-difluorobenzophenone to potassium carbonate is 1:1.2 to 1:2.
[0020] Furthermore, the reaction temperature is 200-240° C., and the reaction time is 10-24 hours.
[0021] The third object of the present invention is to provide the use of the DA type polytriphenylamine compound as described above as a fluorescent probe for detecting TNT content in water and drug budesonide suspension.
[0022] The present invention uses diaromatic amine compounds and difluoroaromatic compounds as raw materials, and successfully prepares a DA type triphenylamine polymer through a one-step CN coupling reaction. The structure and stability of the polymer are characterized by means of infrared, nuclear magnetic resonance, thermal analysis, etc., and its photophysical parameters such as ultraviolet absorption spectrum, fluorescence spectrum, fluorescence lifetime and quantum yield are tested. The molecular configuration, frontier orbital energy level and distribution of the polymer are also carried out, and the auxiliary experimental results jointly reveal the relationship between polymer performance and structure. The DA type polytriphenylamine compound has a high responsiveness to the drug budesonide suspension and can be used for quality detection; in addition, it has a strong luminescent property in water and can be well used for the detection of trace TNT, wherein the detection limit of PTPAK-2 for TNT is 0.25 μmol / L. At the same time, it shows good anti-interference ability and is almost unaffected by other nitro compounds and metal cation potential factors.
[0023] The beneficial effects of the present invention are as follows:
[0024] The DA type polytriphenylamine compound provided by the present invention has the advantages of low detection limit and good detection stability in drug detection such as budesonide suspension and detection of TNT in water; the existing detection methods are not as good as the compound of the present invention, and the preparation method thereof is simple and has a high yield. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1(a) Infrared spectrum of monomer (A: N,N'-diphenylbenzidine; B: N,N'-diphenyl-p-phenylenediamine; C: N,N'-di(2-naphthyl)-p-phenylenediamine; D: 4,4'-difluorobenzophenone); (b) Infrared spectrum of polymer (A: PTPAK-1; B: PTPAK-2; C: PTPAK-3).
[0026] Figure 2 H NMR spectra of the polymers: (a) PTPAK-1; (b) PTPAK-2; (c) PTPAK-3.
[0027] Figure 3 TGA (a) and DSC (b) of the polymer.
[0028] Figure 4 (a) UV-visible absorption spectrum of polymer powder; (b) photograph of the polymer under sunlight.
[0029] Figure 5 (a) Fluorescence spectrum of polymer powder; (b) Photograph of polymer under UV light.
[0030] Figure 6 This is the transient fluorescence decay curve of the polymer powder.
[0031] Figure 7 UV-visible absorption spectra of PTPAK-1 (a), PTPAK-2 (b), and PTPAK-3 (c) in different solvents.
[0032] Figure 8 Fluorescence spectra of PTPAK-1 (a), PTPAK-2 (b), and PTPAK-3 (c) in different solvents.
[0033] Fig. 9 The linear relationship between the Stokes shift (Δν) of PTPAK-1 (a), PTPAK-2 (b), and PTPAK-3 (c) and the orientation polarizability (Δf) of the solvent.
[0034] Fig.10 Changes in fluorescence intensity and maximum emission wavelength of the polymers in different ratios of THF / H2O, (a) PTPAK-1; (b) PTPAK-2; (c) PTPAK-3.
[0035] Fig.11 (a) Detection of TNT by PTPAK-2; (b) Stern-Volmer equation fitting curve of TNT by PTPAK-2.
[0036] Fig.12 The fluorescence intensity changes after adding different nitro compounds and metal ions into PTPAK-2 solution. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is described in detail below in conjunction with the embodiments. It is necessary to point out that the following embodiments are only used to explain and illustrate the present invention and are not used to limit the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above invention content still belong to the protection scope of the present invention.
[0038] Example 1
[0039] 1. Experimental instruments and raw materials
[0040] Table 1 Experimental drugs
[0041]
[0042] Table 2 Main experimental equipment
[0043]
[0044]
[0045] 2. Preparation of polymers
[0046] As shown in the following reaction formula (I), three polytriphenylamine ketone polymers were synthesized by CN coupling, which were respectively denoted as PTPAK-1, PTPAK-2 and PTPAK-3. The specific preparation method is as follows:
[0047]
[0048] The specific preparation method is as follows: under a nitrogen atmosphere, 10 mmol of 4,4'-difluorobenzophenone, 10 mmol of N,N'-diphenylbenzidine and 15 mmol of anhydrous potassium carbonate are added to a three-necked bottle equipped with a stirrer, and then 10 mL of sulfolane and 5 mL of chlorobenzene solution are added dropwise, and the reaction system is stirred to mix evenly, and the reaction is continued at 200°C for 20 hours. After the reaction is completed, the reaction solution is poured into anhydrous ethanol for precipitation, filtered and washed with distilled water several times, and the raw materials and oligomers are completely removed with anhydrous ethanol through a Soxhlet extractor, and vacuum dried for 6 hours to obtain a light gray powder polymer.
[0049] 3. Polymer Characterization and Performance Testing Methods
[0050] (1) Thermal stability
[0051] The DSC and TGA curves of the polymers were obtained by differential scanning calorimeter Netzsch DSC214 and thermal analyzer Mettler TGA2, respectively, in a nitrogen atmosphere at a heating rate of 10 K / min.
[0052] (2) Fluorescence properties in different solvents
[0053] 1 mg of polymer was added into a glass bottle containing 20 mL of different solvents (cyclohexane (HEX), chloroform (TCM), ethyl acetate (EA), dichloromethane (DCM), tetrahydrofuran (THF), N,N-dimethylformamide (DMF), ethanol (EtOH), methanol (MeOH)). After complete dissolution, the polymer was excited with 365 nm ultraviolet light to test the fluorescence spectrum of the polymer in each solvent.
[0054] (3) Fluorescence quantum yield
[0055] Prepare a polymer solution with an absorbance of less than 0.05 at a UV wavelength of 360 nm, and use quinine sulfate solution ( The solvent is 0.05 mol / L H2SO4 aqueous solution) as a reference sample. After using a fluorescence spectrometer to test the fluorescence spectrum of the polymer in this solvent, the quantum yield is calculated using formula (1-1):
[0056]
[0057] In the formula, st and x represent the standard sample and the sample to be tested respectively. is the fluorescence quantum yield, F is the integrated area of the fluorescence peak, f is the absorption factor, and n is the refractive index of the solvent.
[0058] (4) Fluorescence lifetime
[0059] The fluorescence decay curve of the polymer was measured using a transient fluorescence spectrometer, and the fluorescence lifetimes τ1 and τ2 were obtained by second-order exponential fitting. Then, the average fluorescence lifetime (<τ> avg ).
[0060]
[0061] Where τ1 and τ2 are the fluorescence lifetimes obtained by second-order exponential fitting; B1 and B2 are the proportions of the fluorescence lifetime τ1 and τ2, respectively; <τ> avg represents the average fluorescence lifetime.
[0062] (5) Fluorescence properties of polymers in H2O / THF dual solvent system
[0063] Prepare 10 mL of H2O / THF solutions with a ratio of 10:0, 9:1, 8:2, 7:3, 6:4, 5:5, 4:6, 3:7, 2:8, 1:9, and 0:10 (v / v) respectively, and add 100 μL of a 1 g / L polymer solution to each solution in turn. After oscillation and mixing, test the fluorescence spectra of the polymers at different water contents under 365 nm ultraviolet excitation.
[0064] (6) Detection of polymers on drug budesonide suspension and TNT
[0065] Detection of budesonide suspension: Weigh a certain weight of polymer, transfer it to commercially available budesonide suspension, and test the fluorescence spectrum under 365nm ultraviolet light excitation.
[0066] Detection of TNT: Prepare 500mL of 0.01g / L polymer solution (H2O / THF=9:1), take 10mL and add it to a glass bottle, add 0μL, 2.5μL, 5μL, 7.5μL, 10μL, 17.5μL, 25μL, 37.5μL, 50μL, 75μL, 100μL of 1g / L TNT solution respectively, and test the fluorescence spectrum under 365nm ultraviolet light excitation after equilibrium. The Stern-Volmer constant (K) of the polymer for TNT is calculated by fitting equations (1-3) and (1-4). SV ) and limit of detection (LOD).
[0067]
[0068]
[0069] Where I0 is the initial fluorescence intensity of the fluorescent probe before adding TNT, I is the fluorescence intensity after the addition of TNT, [Q] is the concentration of TNT in the sample being tested, and K is sv is the Stern-Volmer constant, C L is the detection limit of the fluorescent probe, and S is 15 times the standard deviation of the blank sample.
[0070] (7) Polymer selectivity for TNT
[0071] First, prepare a 10 mM concentration of metal ion nitrate (Ag + 、Al 3+ , Ca 2+ 、Co 3+ , Cu 2+ , Fe 2+ , Fe 3+ Mg 2+ , Mn 2+ 、Ni 2+ 、Zn2+ ) and nitro compound (o-chloronitrobenzene (CNB), o-nitrophenol (NP), 1,3-dinitrobenzene (DNB), m-nitrobenzene (NT), nitrobenzene (NB), 2,4,6-trinitrotoluene (TNT), 2,4-dinitrotoluene (DNT), octogen (HMX), hexogen (RDX)) solution. Then, prepare 500mL of 0.01g / L polymer solution (THF / water = 1:9). Take 10mL of polymer solution and put it into a glass bottle, and then add 20μL of the prepared metal ion or nitro compound solution to each sample. After the fluorescence is stable, use 365nm ultraviolet light to excite and test its fluorescence spectrum.
[0072] 4. Results and Discussion
[0073] 1. Structural characterization of polymers
[0074] The three prepared polymers were all powdered solids, and their structures were characterized by IR and NMR. Figure 1 The infrared spectra of monomers and polymers are shown in Figure 2. Among the three polymers, the -1 The disappearance of the NH stretching vibration peak belonging to the raw material at 1650cm -1 The stretching vibration peak of the carbonyl group appears near the NMR proton spectra of the three polymers. Figure 2 As shown, due to the presence of a large number of benzene ring structures in their molecular structures, there is a certain degree of overlap in the hydrogen atom peak positions in the NMR spectrum within the range of 6.5-8ppm. However, at high chemical shifts, the hydrogen belonging to the imino group of the raw material has disappeared, which also confirms that the NH bond has completely reacted.
[0075] 2. Study on thermal stability of polymers
[0076] Figure 3 The TGA and DSC curves of the polymers. As can be seen from the figure, polytriphenylamine derivatives with different structures have different thermal stabilities. First, the thermal stability of PTPAK-3, whose side chain is substituted by naphthyl, is much higher than that of the other two polytriphenylamine derivatives, with a thermal decomposition temperature of 536°C and a residual carbon rate of 70.5%. This is because the introduction of a larger naphthyl group on the polymer side chain can inhibit the breakage reaction of the main chain at high temperatures. Among the other two polymers, PTPAK-1 and PTPAK-2 have relatively poor thermal stability, with thermal decomposition temperatures of 339°C and 343°C, respectively. There are significant differences in the thermal stability of polytriphenylamine derivatives containing carbonyl groups, which may be caused by the large difference in molecular weight between different polymers, because the unreacted NH bonds in the end groups may affect the stability of the polymer at high temperatures.
[0077] The DSC curves of the three polymers show that the polymers have obvious glass transition. The glass transition temperatures of the polymers PTPAK-1, PTPAK-2 and PTPAK-3 with carbonyl groups are 160℃, 162℃ and 193℃ respectively.
[0078] 3. Study on the photophysical properties of polymers
[0079] The photophysical properties of fluorescent materials not only reflect their electronic structure and energy level distribution, but are also crucial for a deep understanding and optimization of their fluorescence performance. In particular, the three triphenylamine polymer materials were characterized in detail through UV-visible absorption spectra, fluorescence spectra, fluorescence lifetimes, and quantum yields, so as to objectively evaluate their photophysical properties and provide a basis for further optimization.
[0080] like Figure 4 The UV-visible absorption spectra of the polymer powders are shown in Figure 2. The three polymer powders have strong absorption in the UV range, which is mainly related to their π-π* transition and n-π* transition.
[0081] The fluorescence spectra of the three polymers show their different luminescence properties ( Figure 5 ), the maximum emission wavelengths of the three polymers (λ em ) span is large. PTPAK-1, PTPAK-2 and PTPAK-3 have the phenomenon of red shift in the maximum emission wavelength. This is because the luminescent materials based on the ICT effect are affected by the electron donation-withdrawing effect within the structure. Molecules with stronger electron donation-withdrawing ability have a smaller HOMO-LUMO energy level difference, which leads to lower energy released when the electrons in the excited state return to the ground state, and a longer wavelength.
[0082] The length of the fluorescence lifetime is affected by the transition mode of the material from the excited state to the ground state. The transient fluorescence decay curves of the three polymers were tested using a transient fluorescence spectrometer. The fluorescence lifetimes (τ1 and τ2) of the polymers were obtained by fitting the fluorescence lifetimes through secondary exponentials. The two fluorescence lifetimes represent different transition modes. The average fluorescence lifetime (<τ> avg ).like Figure 6 As shown in Table 3, materials with longer fluorescence lifetimes have a higher proportion of radiative transitions and higher quantum yields.
[0083] Table 3 Quantum yield and fluorescence lifetime of polymer powders
[0084]
[0085] Note: In the table is the absolute quantum yield measured by the fluorescence spectrometer through an integrating sphere. “-” means that the quantum yield is less than 0.01 and it is difficult to measure the specific value through an integrating sphere. τ1 and τ2 are the fluorescence lifetimes of the second-order exponential fitting. avg is the average fluorescence lifetime.
[0086] The photophysical properties of polymers in different solvents were studied, such as Figure 7 The UV-visible absorption spectra of the three polymers in n-hexane (HEX), chloroform (TCM), ethyl acetate (EA), dichloromethane (DCM), tetrahydrofuran (THF), N,N-dimethylformamide (DMF), ethanol (EtOH) and methanol (MeOH) are shown. The three polymers all have two absorption peaks. Their absorption bands in the short-wave direction are attributed to the π-π* transition of the benzene ring, while the absorption bands in the long-wave direction are ICT absorption bands. The ICT band in the UV-visible absorption spectra of PTPAK-1, PTPAK-2 and PTPAK-3 appears near 390nm and is significantly separated from the π-π* transition absorption band. In addition, the maximum absorption wavelengths of the three polymers are affected by the polarity of the solvent.
[0087] Figure 8 The fluorescence spectra of three polymers in solvents of different polarities. The three polymers show significant differences in maximum emission wavelengths in solvents of different polarities, which is a characteristic of luminescent materials based on the ICT effect. In low-polarity solvents (HEX), the maximum emission wavelength is 446nm, while in high-polarity solvents (DMF), the maximum emission wavelength is 556nm, and there is a 90nm emission wavelength shift between the two. Only PTPAK-1, which has a different electron-withdrawing structure, shows a stronger solvent color change effect, with a maximum emission wavelength of 438nm in HEX and a maximum emission wavelength of 586nm in DCM, and there is a 138nm emission wavelength shift between the two. This is due to the presence of a donor-acceptor structure in the polymer structure, which can achieve charge transfer (CT) from electron donors to electron acceptors in the excited state. The CT process will significantly increase the dipole moment of the excited state, and high-polarity solvents have a more significant effect on the stability of excited states with higher dipole moments, which can reduce the excited state energy to a certain extent, causing the emission wavelength to redshift. The maximum emission wavelength is affected by the polarity of the solvent, and when the electron donation structure is the same, the maximum absorption wavelength of polymers such as polytriphenylamine is greatly affected by the solvent. This may be because polytriphenylamine has a stronger DA effect and a higher dipole moment in the CT state, making it more sensitive to solvent polarity.
[0088] It is worth noting that the quantum yields in different solvents (Table 4) show that the quantum yield of the polymer in high-polarity solvents is significantly lower than that in medium- and low-polarity solvents. This is due to the stronger solute-solvent interaction in high-polarity solvents. The dissipation of excited state energy in a non-radiative transition manner will significantly weaken the polymer fluorescence.
[0089] Table 4 Photophysical properties of PTPAK-1 in different solvents
[0090]
[0091] In order to better describe the effect of solvent polarity on the photophysical properties of polymers, the physical parameter of solvent orientation polarizability (Δf) is introduced, and Stokes shift (Δν) is used to represent the change of polymer photophysical properties. The Lippert-Mataga equation (Equation 1-5) is used to linearly fit Δf and Δν to further study the color change behavior caused by solvent polarity. Fig. 9 As shown, the Δf of different solvents is linearly fitted with the Stokes shift (Δν) data of PTPAS in the corresponding solvents. In general, when the ICT state does not exist, the fitting slope is almost equal to zero; when the ICT state is the main excited state, the fitting slope is greater than zero. The data processing results show that the linear relationship between Δν and Δf is poorly fitted, but the overall trend is that the greater the polarity of the solvent, the greater its Stokes shift. These results indicate that the excited state of PTPAK-1 in different solvents may exist in both the local excited (LE) state and the intramolecular charge transfer (ICT) state. The complexity of the relationship between the two competing excited states will lead to a deterioration in the linear relationship fitted using the Lippert-Mataga equation.
[0092]
[0093] Where Δν is the Stokes shift of the polymer; Δf is the orientation polarizability of the solvent; ε0 is the dielectric constant of vacuum; h is Planck's constant; c is the speed of light; r 2 is the radius of the solvent cage where the fluorescent body is located; Const. is a constant.
[0094] The fluorescence properties of the polymer in the THF / H2O dual solvent system are as follows: Fig.10As shown in the figure, the three polymers all show a trend of decreasing fluorescence at low water content. This is because when the water content is low, the fluorescence of the polymer is mainly affected by the polarity of the solvent. When the water content in tetrahydrofuran is continuously increased (0%-50%), due to the continuous increase in solvent polarity, the conformational changes and solute-solvent interactions of the ICT-based luminescent polymer in the excited state are strengthened, resulting in a continuous weakening of the fluorescence and a significant change in the emission wavelength. When the water content is further increased (50%-70%), due to the continuous aggregation of particles in the solution, the luminescence mechanism gradually changes from liquid luminescence to solid nanoparticle luminescence. Since the distorted spatial structure of the polymer has a certain inhibitory effect on the accumulation of fluorophores in the aggregated state, a small enhancement of the solution fluorescence is observed at this stage. When the water content is higher (70%-99%), due to the intensified aggregation of the polymer in the solution, its fluorescence intensity will be weakened to a certain extent. In addition, PTPAK-2 ( Fig.10 Figure (b) shows a phenomenon different from the other two polymers. As the water content increases, the fluorescence intensity of PTPAK-2 shows a trend of first increasing and then decreasing. The reason for the fluorescence enhancement phenomenon in the water content range of 0%-20% may be that the change in the solvent mixing ratio causes other interactions, while the fluorescence quenching phenomenon in the range of 20%-99% is a typical aggregation-induced quenching (ACQ) phenomenon, which is caused by its geometric structure.
[0095] Table 5 Fluorescence quantum yields of three polymers in tetrahydrofuran and water
[0096]
[0097] Table 5 shows the fluorescence quantum yield data of the polymers in tetrahydrofuran and water. It can be seen that the three polytriphenylamine ketones (PTPAK-1, PTPAK-2 and PTPAK-3) can maintain 30% to 40% of the quantum yield in tetrahydrofuran in water.
[0098] 4. Detection of TNT by polymer
[0099] The limit of detection (LOD) is an important indicator for evaluating the performance of fluorescent probes. Three polytriphenylamine ketones (PTPAK-1, PTPAK-2 and PTPAK-3) have good fluorescence properties in water and are used to detect trace amounts of TNT in water. Fig.11 In a, the fluorescence intensity of the polymer solution gradually weakened with increasing TNT concentration in the solution. When the TNT concentration was 1.1 μM, PTPAK-2 quenched 30% of the initial fluorescence intensity; when the TNT concentration reached 11 μM, PTPAK-2 achieved 80% fluorescence intensity quenching. The curve was fitted by the Stern-Volmer equation ( Fig.11As can be seen in b), when the TNT concentration is lower than 11 μM, the ratio of the initial fluorescence intensity to the fluorescence intensity after quenching equilibrium (I0 / I) and the TNT concentration (c TNT ) showed a good linear relationship. When the TNT concentration was higher than 11 μM, I0 / I and c TNT The relationship gradually deviates from linearity, which is because the Stern-Volmer equation is not applicable when the concentration of the test substance is too high. The test results show that the Stern-Volmer constant (K SV )1.66×10 5 M -1 , the limit of detection (LOD) was 0.25 μmol / L, which represented that PTPAK-2 had excellent fluorescence response characteristics to TNT (Table 6).
[0100] Table 6 Performance comparison of PTPAK and reported TNT fluorescent probes
[0101]
[0102] [1]Xu YW,Zhong C,Zhang BY,et al.Facile preparation oftetraphenylethylene-based porous polymer with dual role of adsorption and detection for trinitrotoluene[J].Polymer,2023,288:126454.
[0103] [2]Mukherjee A,Bhattacharya S,Chakravarty M.An unprecedentedpyridine-based dinuclear mixed-valent ReI / VII oxo-bridged complex:asolvatochromic and AIE-active probe for nanomolar detection of picric acidand trinitrotoluene[J].Dalton Transactions,2021,50(26):9144-9157.
[0104] [3]Liao Y,Hu L,Huang J,et al.A facile and novel AIE vesicle asnanoprobe for simple and rapid detection of TNT in water[J].SpectrochimicaActa Part A:Molecular and Biomolecular Spectroscopy,2024,307:123617.
[0105] [4]Dong W,Fei T,Scherf U.Conjugated polymers containingtetraphenylethylene in the backbones and side-chains for highly sensitive TNTdetection[J].RSC Advances,2018,8(11):5760-5767.
[0106] [5]Dong W,Ma Z,Chen P,et al.Carbazole and tetraphenylethylene basedAIE-active conjugated polymer for highly sensitive TNT detection[J].MaterialsLetters,2019,236:480-482.
[0107] [6]Komikawa T,Tanaka M,Tamang A,et al.Peptide-functionalized quantumdots for rapid label-free sensing of2,4,6-trinitrotoluene[J].BioconjugateChemistry,2020,31(5):1400-1407.
[0108] [7] SK.Pyrene substituted amphiphilic ROMP polymers asnano-sized fluorescence sensors for detection ofTNT in water[J].Polymer,2019,183:121868.
[0109] [8]Doan BK, Tran TVT, Nguyen TH, et al. One-pot synthesis of star-shapedconjugated oligomers based on 3-hexylthiophene, pyrene and triphenylamine as TNT chemosensors[J]. Journal of Photochemistry and Photobiology A: Chemistry, 2020, 394: 112496.
[0110] 5. Study on the selectivity of polymers for TNT
[0111] like Fig.12 As shown in Figure 2, different nitro compounds (CNB, DNB, DNT, HMX, NB, NP, NT, RDX) and metal ions (Ag + 、Al 3+ , Ca 2+ 、Co 3+ , Cu 2+ , Fe 2+ , Fe 3+ Mg 2+ , Mn 2+ 、Ni 2+ 、Zn 2+ ) potential interferents to investigate the selectivity of the material for TNT. The fluorescence of PTPAK-2 was less affected by common nitro compounds and metal ions, but showed a significant quenching response to TNT. The insensitivity of PTPAK-2 to common interferents indicates that it has a wide range of application potential.
[0112] 6. Conclusion
[0113] Three polytriphenylamine ketones (PTPAK-1, PTPAK-2, PTPAK-3) were successfully synthesized by CN coupling reaction with commercial raw materials. The structures and thermal stability of the three polymers were characterized by infrared, nuclear magnetic resonance, and thermal analysis. The relationship between the performance and structure of the three polymers was analyzed in detail by testing the UV-absorption spectrum, fluorescence spectrum, fluorescence lifetime, and quantum yield of the three polymers in various states.
[0114] The results showed that DA-type triphenylamine polymer can be well used for the detection of drug budesonide suspension and trace TNT in water. It has a good fluorescence quenching response to budesonide suspension. The detection limit (LOD) of PTPAK-2 for TNT in water is 0.25 μmol / L, and it is almost unaffected by other nitro compounds and metal cations.
Claims
1. A DA type polytriphenylamine ketone compound, characterized in that: The structural formula of the DA type polytriphenylamine compound is shown in the following formula <Ⅰ>: Wherein, Ar1 is Ar2 is X is n is a repeating unit.
2. The DA type polytriphenylamine ketone compound according to claim 1, characterized in that: The average life span <τ>avg of the DA-type polytriphenylamine compound is 1.29 to 1.67, and the fluorescence quantum yield in water is It is 0.01~0.
06.
3. The DA type polytriphenylamine ketone compound according to claim 1, characterized in that: The thermal decomposition temperature of the DA type polytriphenylamine compound is 339-536°C, and the glass transition temperature is 160-193°C.
4. The DA type polytriphenylamine ketone compound according to claim 1, characterized in that: The DA type polytriphenylamine compound has a fluorescence quenching response to the drug budesonide suspension, the detection limit of TNT can reach 0.25 μmol / L, and is not affected by other nitro compounds and metal cation potential factors.
5. The method for preparing the DA type polytriphenylamine ketone compound according to any one of claims 1 to 4, characterized in that: It is prepared in a nitrogen atmosphere by a one-step CN coupling reaction using 4,4'-difluorobenzophenone, diaromatic imine compounds and potassium carbonate.
6. The preparation method according to claim 5, characterized in that: The diaromatic imine compounds include N,N'-diphenylbenzidine, N,N'-diphenyl-p-phenylenediamine or N,N'-di(2-naphthyl)-p-phenylenediamine.
7. The preparation method according to claim 5, characterized in that: The molar ratio of the 4,4'-difluorobenzophenone to the diaromatic imine compound is 1:
1.
8. The preparation method according to claim 5, characterized in that: The molar ratio of the 4,4'-difluorobenzophenone to potassium carbonate is 1:1.2 to 1:
2.
9. The preparation method according to claim 5, characterized in that: The reaction temperature is 200-240° C., and the reaction time is 10-24 hours.
10. Use of the DA-type polytriphenylamine compound according to any one of claims 1 to 4 and the DA-type polytriphenylamine compound prepared by the method according to any one of claims 5 to 9 as a fluorescent probe for detecting TNT content in water and detecting drug budesonide suspension.
